2016
DOI: 10.1007/s11164-016-2587-7
|View full text |Cite
|
Sign up to set email alerts
|

Montmorillonite K10: an effective catalyst for synthesis of 2-aminothiazoles

Abstract: An efficient one-pot synthesis of 2-aminothiazoles from methylcarbonyl and thiourea has been developed using montmorillonite-K10 as a catalyst at 80°C in DMSO medium. A plausible mechanism is proposed in which a-iodomethylcarbonyls are formed via methylcarbonyls as raw material using iodine as iodination reagent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 32 publications
1
4
0
Order By: Relevance
“…Based on the results of our experiments and previous literature, [18][19][20][21][22][23][24][25] we propose the following reaction pathway (Scheme 1). Briefly, acetophenone (1a) is converted into α-iodoketone A in the presence of the I 2 catalyst.…”
supporting
confidence: 56%
See 1 more Smart Citation
“…Based on the results of our experiments and previous literature, [18][19][20][21][22][23][24][25] we propose the following reaction pathway (Scheme 1). Briefly, acetophenone (1a) is converted into α-iodoketone A in the presence of the I 2 catalyst.…”
supporting
confidence: 56%
“…18 Subsequently, various modified Hantzsch methods have been developed such as using heterogeneous catalysts, microwave heating, solid synthesis, or greener solvents including ionic liquids, PEG-400, and water. [19][20][21][22][23][24][25] Other synthetic methods toward 2-aminothiazoles have utilized different coupling partners such as phenyl thiocyanates and propargylamines, alkyne(alkene)-substituted iodine(III) reagents and thioureas, 1,2-dicyano-3-bromo-2-phenylpropenes and thioureas, and α-SCN-substituted ketones and amines. [26][27][28][29] However, the preparation of these coupling materials is generally difficult, needing multiple steps and harsh reaction conditions.…”
mentioning
confidence: 99%
“…The porosity presented by Cat C mainly results from its interparticle porosity (Figure 7c). Then, Cat B presents a substantially higher specific surface area (Table 5) that is a consequence of the presence of the MK10 clay, a well-known and catalytically applied layered aluminosilicate [76,77], which was added during the synthesis of Cat B and possesses a superficial area close to 250 m 2 g −1 [78]. Consequently, over the specific surface area of the MK10 clay, the lower amount of the supported catalytically active metallic species is highly dispersed, a behavior that was confirmed by its XRD diffractogram (Figure 3), which does not show metallic oxide diffraction peaks.…”
Section: Resultsmentioning
confidence: 99%
“…Structures containing 2-aminothiazole moiety are an important class in the family of heterocyclic compounds and have many potential applications especially in medicinal chemistry because of their anti-cancer and anti-tumor, anti-viral, anti-inammatory, and antimicrobial activities. [53][54][55] Moreover, these compounds can be used as convenient substrates to prepare more complex products like corresponding azo derivatives 56 and many polycyclic heterocyclic compounds. 57,58 In 2017, our team at the University of Kashan found that simple starch can promote the synthesis of 2-aminothiazole derivatives in the presence of molecular iodine as a halogenating agent (Scheme 2).…”
Section: Simple Starchmentioning
confidence: 99%